Transcutaneous cervical vagal nerve stimulation modulates cardiac vagal tone and tumor necrosis factor‐alpha. Issue 5 (12th December 2016) - Brock, C.; Brock, B.; Aziz, Q.; Møller, H. J.; Pfeiffer Jensen, M.; Drewes, A. M.; Farmer, A. D.
Abstract: The vagus nerve is a central component of cholinergic anti‐inflammatory pathways. We sought to evaluate the effect of bilateral transcutaneous cervical vagal nerve stimulation (t‐VNS) on validated parameters of autonomic tone and cytokines in 20 healthy subjects. 24 hours after t‐VNS, there was an increase in cardiac vagal tone and a reduction in tumor necrosis factor‐α in comparison to baseline. No change was seen in blood pressure, cardiac sympathetic index or other cytokines. These preliminary data suggest that t‐VNS exerts an autonomic and a subtle antitumor necrosis factor‐α effect, which warrants further evaluation in larger controlled studies. Abstract : In healthy humans, we found that transcutaneous electrical vagal nerve stimulation increases cardiac vagal tone and decreases tumor necrosis factor‐alpha. These preliminary findings warrant further investigation in patients with immune mediated inflammatory disorders such as inflammatory bowel disease. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility-may-2017/id1218867696 Youtube:https://youtu.be/div-oROGrz0